2011
DOI: 10.1245/s10434-011-1707-2
|View full text |Cite
|
Sign up to set email alerts
|

Ductal Carcinoma-In-Situ of the Breast with Subsequent Distant Metastasis and Death

Abstract: DM after a diagnosis of pure DCIS is rare. Although most patients with DM have a preceding invasive LRR, some present with subsequent DM alone. Further study is required to identify clinical and pathologic predictors of this more rapid disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 17 publications
1
39
0
Order By: Relevance
“…Of the 8 cases of direct metastasis, 6 had tumour sizes C20 mm. Progression from DCIS to metastasis is an indication of aggressive biological behaviour [53]. In our patients with direct distant metastasis, only 2 were from the screen-detected group, while the rest were symptomatic cases, suggesting that symptomatic DCIS is more likely to recur and even potentially metastasise.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Of the 8 cases of direct metastasis, 6 had tumour sizes C20 mm. Progression from DCIS to metastasis is an indication of aggressive biological behaviour [53]. In our patients with direct distant metastasis, only 2 were from the screen-detected group, while the rest were symptomatic cases, suggesting that symptomatic DCIS is more likely to recur and even potentially metastasise.…”
Section: Discussionmentioning
confidence: 75%
“…DCIS is, by definition, not invasive and therefore theoretically unable to metastasise to regional lymph nodes [52]. Roses et al [53] documented a distant metastases rate of 1.0 % after an initial diagnosis of pure DCIS, where some of the patients also had no prior invasive locoregional recurrences. Donker et al [15] also disclosed 3.2 % of direct distant metastasis in their study cohort.…”
Section: Discussionmentioning
confidence: 99%
“…However, different behaviors have been observed after the initial treatment; some DCISs remain indolent or are associated with a low risk of developing into invasive cancer, whereas others show a higher tendency to progress to invasive breast cancer or to recur (3). Published reports have shown that rates of recurrence after treatment for pure DCIS range from 5% to 20%, and approximately 50% of these are invasive (4,5).…”
mentioning
confidence: 99%
“…There is a general consensus that DCIS represents a noninvasive, nonobligate precursor of invasive breast cancer (11). Therefore, the early diagnosis and management of DCIS are critical in preventing the development of invasive cancer (12,13). It has been proposed that the biological aggressiveness of breast cancer can also be predicted by mammographic characteristics (13,14).…”
Section: Introductionmentioning
confidence: 99%